2022
DOI: 10.3389/fnagi.2022.810125
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Multilevel Classification of Alzheimer’s Disease Using Non-invasive Functional Near-Infrared Spectroscopy

Abstract: The timely diagnosis of Alzheimer’s disease (AD) and its prodromal stages is critically important for the patients, who manifest different neurodegenerative severity and progression risks, to take intervention and early symptomatic treatments before the brain damage is shaped. As one of the promising techniques, functional near-infrared spectroscopy (fNIRS) has been widely employed to support early-stage AD diagnosis. This study aims to validate the capability of fNIRS coupled with Deep Learning (DL) models fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…The unit of hemoglobin concentration was set to be mM/DPF, which is equivalent to setting DPF as 1 at different wavelengths [ 24 ]. Note that considering DPF as a part of the unit of hemoglobin concentration is one of the widely accepted approaches [ 12 , 24 , 25 , 28 ]. In this study, 808 nm was selected because it is known as one of the isosbestic points of the extinction coefficients of and [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unit of hemoglobin concentration was set to be mM/DPF, which is equivalent to setting DPF as 1 at different wavelengths [ 24 ]. Note that considering DPF as a part of the unit of hemoglobin concentration is one of the widely accepted approaches [ 12 , 24 , 25 , 28 ]. In this study, 808 nm was selected because it is known as one of the isosbestic points of the extinction coefficients of and [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among various optical techniques, diffuse optical spectroscopy (DOS), also known as near-infrared spectroscopy (NIRS) in biomedical engineering, is frequently used in AD studies due to its relatively high temporal resolution, low cost, portability, and non-invasiveness. In most NIRS-based AD studies, experimental protocols, including the verbal fluency test [ 7 , 8 , 9 , 10 , 11 , 12 ], N-back test (including 1-back) [ 10 , 11 , 12 , 13 ], oddball test [ 11 , 12 ], and Stroop test [ 10 ], are used as stimuli to the brain. Such approaches aim to test neurovascular coupling to hypothesize differences in the responses of an AD group and a normal group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ho et al. 83 attempted to use fNIRS and DL techniques to distinguish not only between healthy and prodromal Alzheimer’s afflicted subjects but also subjects with asymptomatic Alzheimer’s disease and dementia due to Alzheimer’s disease. Not only did this study try to distinguish between different stages of Alzheimer’s disease, the study used a notably large sample size of 140 participants, which was larger than any other study reported in this review as shown in Table 2 .…”
Section: Applications In Fnirsmentioning
confidence: 99%
“…Using resting state fNIRS data, the network with the highest accuracy, VGG19, achieved an accuracy of 97.01% when connectivity maps were used as the input, outperforming the conventional machine learning techniques, with LDA classifier reporting the highest accuracy of 67.00%. Ho et al 83 attempted to use fNIRS and DL techniques to distinguish not only between healthy and prodromal Alzheimer's afflicted subjects but also subjects with asymptomatic Alzheimer's disease and dementia due to Alzheimer's disease. Not only did this study try to distinguish between different stages of Alzheimer's disease, the study used a notably large sample size of 140 participants, which was larger than any other study reported in this review as shown in Table 2.…”
Section: Diagnostic Toolsmentioning
confidence: 99%